APLIKASI SISTEM INFORMASI KURSUS MENGEMUDI BERBASIS WEB ( STUDI KASUS : KURSUS SETIR MOBIL SANTA ) - Naufal Ryandhika Mahdy; Gilland Kasyrafurhman; Bagas Ramadhan; Dwi Ade Handayani Capah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
The course is one of the education provided outside the official school (non-formal) to develop self-ability and skills. Santa Car Driving Course is a skills education institution that specializes its students to be proficient in driving a car. However, the institution still registers courses by coming to the institution's location. This study aims to provide an application that helps institutions in providing course schedule information and online course registration. The method used in making this application is the PIECES method for running system analysis and the waterfall method for system requirements analysis. The result of this research is an application that is able to provide information on course schedules, registration, attendance and report notes.